2011
DOI: 10.1063/1.3647773
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deep accepters in ZnO nanowires induced by ammonia plasma

Abstract: Nitrogen doping in ZnO nanowires was achieved through ammonia plasma treatment followed by thermal annealing. The strong dependence of the red light emission from the nanowires excited by 2.4 eV on the nitrogen concentration, suggests that the red light emission originates from nitrogen related defects. The mechanism responsible for the red light emission is in good agreement with the deep-acceptor model of nitrogen defects, clarifying that nitrogen atoms caused deep accepters in ZnO nanowires. Based on this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Each solid line represents the sum of three Lorentzian peaks at a particular temperature based on a fitting procedure as discussed in more detail below. A sharp UV peak and a broad band can be clearly seen, similar to what other groups have observed from ZnO films deposited on conductive glass via ECD or on Si substrates using either chemical vapor transport or hydrothermal processing with ZnO nanocrystals acting as the seeds .…”
Section: Resultssupporting
confidence: 84%
“…Each solid line represents the sum of three Lorentzian peaks at a particular temperature based on a fitting procedure as discussed in more detail below. A sharp UV peak and a broad band can be clearly seen, similar to what other groups have observed from ZnO films deposited on conductive glass via ECD or on Si substrates using either chemical vapor transport or hydrothermal processing with ZnO nanocrystals acting as the seeds .…”
Section: Resultssupporting
confidence: 84%
“…The N O was widely considered as a shallow acceptor for a long time. However, recent calculations demonstrated that the N O has an exceedingly high ionization energy of 1.3 eV [31], supported by the experimental results of Huang et al [32], which means N O is not the natural candidate for explaining the observed A 0 X. Lately, more and more papers have a tendency to assign the unidentified shallow acceptor to a native - extrinsic complex or native defect cluster complex, including 2V Zn  − D Zn (D = P, As, Sb) [33, 34], V Zn  − N O [13], 2V Zn  − V O [35], 3V Zn  − D i (D = P, As, Sb) [36], and V Zn clusters [16].…”
Section: Resultsmentioning
confidence: 68%
“…In this paper, we utilized a plasma‐treatment process to prepare N‐doped ZnO single crystal at room temperature. Several studies concerning the effects of ammonia or hydrogen plasma post‐treatment on ZnO could be found in the literature . This is the first report of the nitrogen plasma post‐treatment on ZnO single crystal.…”
Section: Introductionmentioning
confidence: 95%